Agama dan Fenomena Sosial Kontemporer: Kajian Sosiologi Agama Atas Konflik, Bunuh Diri, dan Kecerdasan Buatan - Tjang, Yanto Sandy; Soeryamassoka, Herkulana Mekarryani (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2025)
Religious Sociology is a crucial discipline for understanding religion as a dynamic social phenomenon within the complexity of contemporary society. This study aims to analyze the scope and object of religious sociology, assess its significance for theology students, and examine the relevance of integrating classical and contemporary sociological paradigms to understand current social phenomena, such as suicide, religious conflict, and the development of artificial intelligence. Employing a descriptive qualitative approach based on literature review, with thematic analysis and comparative synthesis, the study finds that religious sociology provides an analytical framework capable of integrating structural, cultural, and symbolic dimensions, which are often overlooked by individualistic or normative theological approaches. These findings underscore the strategic importance of religious sociology as a conceptual bridge between theological reflection and social reality, while also demonstrating its relevance in addressing challenges related to pluralism, conflict, and transformations in religiosity in the digital and artificial intelligence era.